2007
DOI: 10.1534/genetics.107.075283
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation of ebony Gene Controlling Thoracic Pigmentation in Drosophila melanogaster

Abstract: We identified the causal genetic variation for the difference in the thoracic trident pigmentation intensity between two wild-derived strains of Drosophila melanogaster. It was found to be the difference in expression level of ebony, which codes for an enzyme in the melanin-synthesis pathway and has pleiotropic effects on vision and behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 28 publications
4
47
0
Order By: Relevance
“…Studies in Drosophila and Tribolium have shown that ebony plays the central role in suppressing black pigmentation (Figure 1). On loss of function of ebony, a global darkening of body pigmentation was observed in both species (Wittkopp et al 2002b;Takahashi et al 2007;Tomoyasu et al 2009). Based on these observations, we expected ebony RNAi Oncopeltus adults to exhibit black coloration throughout the body.…”
Section: Melanin Patterning In Oncopeltus 405mentioning
confidence: 99%
“…Studies in Drosophila and Tribolium have shown that ebony plays the central role in suppressing black pigmentation (Figure 1). On loss of function of ebony, a global darkening of body pigmentation was observed in both species (Wittkopp et al 2002b;Takahashi et al 2007;Tomoyasu et al 2009). Based on these observations, we expected ebony RNAi Oncopeltus adults to exhibit black coloration throughout the body.…”
Section: Melanin Patterning In Oncopeltus 405mentioning
confidence: 99%
“…Some direct evidences linking this gene to the thoracic or abdominal pigmentation variation in natural populations were put forward by an associated linkage pattern in the 5' upstream region of this gene (Pool and Aquadro, 2007), a genetic mapping result using two wild-derived dark and light strains (Takahashi et al, 2007), and quantitative comparisons of the transcription levels induced by cisregulatory elements from strains with different pigmentation intensities (Rebeiz et al, 2009). The lower expression of this gene in developing epidermis is associated with darker pigmentation, and the higher expression with lighter pigmentation (Takahashi et al, 2007;Rebeiz et al, 2009). This association is reported in populations from Africa (Rebeiz et al, 2009), Australia (Telonis-Scott et al, 2011, and southern Japan (Takahashi and TakanoShimizu, 2011).…”
Section: Pigmentation Variation In D Melanogastermentioning
confidence: 99%
“…Recent studies have shown that the major causal genetic differences underlying naturally occurring pigmentation variation in D. melanogaster lie in the cisregulatory region of ebony (Pool and Aquadro, 2007;Takahashi et al, 2007;Rebeiz et al, 2009;Telonis-Scott et al, 2011;Takahashi and Takano-Shimizu, 2011). This leads us to a question why ebony, among other structural genes in the melanin biosynthesis pathway, has been subjected to frequent changes or possibly the target of natural selection in this species.…”
Section: Perspectivesmentioning
confidence: 99%
“…Wittkopp, personal communication), by ebony and yellow in D. elegans and D. gunungcola (S. Yeh and J. True, personal communication), and by ebony in some populations of D. melanogaster (Pool and Aquadro 2007;Takahashi et al 2007). Again, none of these loci make a detectable contribution to the difference in pigmentation between D. m. malerkotliana and D. m. pallens.…”
Section: Resultsmentioning
confidence: 99%